Pharmacological Benefits of Triphala: A Perspective for Allergic Rhinitis - Jantrapirom, Salinee; Hirunsatitpron, Pannaphak; Potikanond, Saranyapin; Nimlamool, Wutigri; Hanprasertpong, Nutthiya (Frontiers in Pharmacology, 2021)
Allergic rhinitis (AR) is considered a major nasal condition impacting a large number of people around the world and which is now becoming a global health problem. Because the underlying mechanisms of AR are complex, development of a single drug treatment might not be enough to treat a wide spectrum of the disease. Although the standard guidelines classify and provide suitable diagnosis and treatments, the vast majority of people with AR are still without any means of controlling it. Moreover, the benefits of AR drugs are sometimes accompanied by undesirable side effects. Thus, it is becoming a significant challenge to find effective therapies with limited undesirable side effects for a majority of patients suffering from uncontrolled AR. Aller-7/NR-A2, a polyherbal formulation, has revealed promising results in patients by reducing nasal symptoms and eosinophil counts without serious adverse effects. Interestingly, three out of seven of the herbals in the Aller-7/NR-A2 formulation are also found in an Ayurvedic polyherbal formulation known as “Triphala,” which is a potential candidate for treatment of AR. However, there are no current studies that have examined the effects of Triphala on the disease. This review aims to describe the complexity of AR pathophysiology, currently available treatments, and the effects of Triphala on AR in order to help develop it as a promising alternative treatment in the future.